2002
DOI: 10.1089/108705702320351187
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cytotoxicity Evaluation in Anticancer Drug Screening of Fractionated Plant Extracts

Abstract: Chosen to reflect biodiversity in a phylogenetic sense, 100 fractionated plant extracts were screened in vitro for cytotoxicity following extraction and fractionation (polypeptide isolation). Of these 100 extracts, 30 were selected and then characterized preliminarily for antitumor potency and mode of action by testing them on two cell lines and primary cultures of human tumor cells. On the basis of cytotoxicity potency, 10 of the extracts were further characterized for anticancer activity in 10 human tumor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 0 publications
0
52
0
3
Order By: Relevance
“…Cycloviolacin O2 is a small cyclic cystine‐rich protein isolated from the sweet violet ( Viola odorata L.), which has been shown to exert significant structure‐dependent cytotoxicity to human cancer cell lines in vitro 1, 2. The protein consists of 30 amino acids and is a member of the cyclotide family, a group of genetically encoded plant proteins with a continuous cyclic backbone 3, 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cycloviolacin O2 is a small cyclic cystine‐rich protein isolated from the sweet violet ( Viola odorata L.), which has been shown to exert significant structure‐dependent cytotoxicity to human cancer cell lines in vitro 1, 2. The protein consists of 30 amino acids and is a member of the cyclotide family, a group of genetically encoded plant proteins with a continuous cyclic backbone 3, 4.…”
Section: Introductionmentioning
confidence: 99%
“…Cycloviolacin O2 has been subject to extensive cytotoxicity testing in vitro, with promising results that warranted further studies 1, 2, 8. In a panel of 10 human cancer cell lines, cycloviolacin O2 showed cytotoxicity to all the cell lines at concentrations in the low‐micromolar range.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic oral toxicity study was done according to OECD guideline 423. [2627] In this experiment, two groups of Wistar rats ( n = 6) were used. Animals were kept on fast overnight with water ad libitum and food was withheld for 3–4 h after the oral administration of the extracts.…”
Section: Methodsmentioning
confidence: 99%
“…Synthetic chemotherapy can potentially cause serious side effects, the toxicity associated with the conventional cancer chemotherapy arises primarily from the lack of specificity for tumor cells. Most of the currently available anticancer drugs are designed to have selective toxicity towards rapidly dividing cells [3]. It is reported that natural compound(s) especially of plant origin, with selective cytotoxicity against specific tumor cell line, can offer either prophylaxis (chemoprevention) or a relatively safer treatment option with minimum side effect [4].…”
Section: Introductionmentioning
confidence: 99%